A novel lab-scale batch foaming equipment: The mini-batch. (September 2016) - Tammaro, D; Contaldi, V; Carbone, MG Pastore; Di Maio, E; Iannace, S
In this paper, we report the design of a new experimental apparatus for the study of the foaming process of thermoplastic polymers with physical blowing agents. The novel lab-scale batch foaming equipment is capable of achieving accurate control of the processing variables, namely, the temperature, the saturation pressure and the pressure drop rate and, furthermore, of allowing the achievement of very high pressure drop rates, the observation of the sample while foaming and the very fast extraction of the foamed sample. By recalling the considerations discussed by Muratani et al. ( J Cell Plast 2005; 24: 15), the design converged into a simple, cheap, and very small pressure vessel, thereby denoted as mini-batch. We herein describe the overall design path of the mini-batch, its characteristics, configurations, together with some examples of use with polystyrene and CO2 as the blowing agent.